2022
DOI: 10.3390/ijerph191912769
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Occurrence of Frailty Syndrome in Hospitalized Older Patients

Abstract: Frailty syndrome (FS) is a condition characterized by a decline in reserves, observed with aging. The most important consequences of the frailty syndrome include disability, hospitalization, fractures, institutionalization, and early mortality. The aim of this study was to identify the most important risk factors for FS in a group of older hospitalized patients in Poland. A total of one hundred and forty-one (78 women, 63 men) elderly patients from the Departments of Internal Medicine of the Medical University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…There are also many studies at home and abroad that reported that age is one of the independent risk factors for frailty. 12 , 13 Some Chinese scholars analyzed the risk factors of frailty in 3836 cases of geriatric internal medicine patients and found that aging is the risk factor of frailty. 8 Our research also confirms this.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many studies at home and abroad that reported that age is one of the independent risk factors for frailty. 12 , 13 Some Chinese scholars analyzed the risk factors of frailty in 3836 cases of geriatric internal medicine patients and found that aging is the risk factor of frailty. 8 Our research also confirms this.…”
Section: Discussionmentioning
confidence: 99%
“…In the other Polish studies on hospital inpatients, the incidence of frailty syndrome assessed using the Fried criteria was 54.2% [ 25 ], using the Edmonton scale—12.3% (mean age 62.6+/−9.7y) [ 36 ], and SHARE-FI (mean age 73 (68–81)y) − 39% [ 37 ]. In another Polish study, in patients hospitalized due to heart failure (mean age 71.6 ± 10.9 years), frailty frequency using the Tilburg Frailty Indicator scale was 71.62% [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an observational study with patients presenting to an Irish Emergency Department (ED) study found no correlation with age 16 . Lower education and socioeconomic status, and living alone were found to be associated with frailty in one study including a mix of community-dwelling and nursing home participants 15 ; while another study in hospitalised older patients found no significant associations 25 . In a study with 22 institutionalised older adults in Italy (mean age 84), frailty as assessed by SHARE-FI was associated with more variance and cross-correlation in self-rated physical, mental, and social health over 100 consecutive days 26 .…”
Section: Associated Factorsmentioning
confidence: 94%
“…Outside community settings, age was also found to be positively correlated with frailty 15,25 . However, an observational study with patients presenting to an Irish Emergency Department (ED) study found no correlation with age 16 .…”
Section: Associated Factorsmentioning
confidence: 95%